2016
DOI: 10.1177/0301006616629036
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Letter Design Features and Aging on Legibility

Abstract: We examined how letter legibility is affected by letter design features (size, contrast, font-type, and complexity), and how this changes with age (by comparing younger [N = 54] and older participants [N = 54]). Types of letters in the study were Japanese characters, Latin alphabets, and digits. Participants verbally reported the letter presented on a Cathode Ray Tube (CRT) display in natural viewing conditions. The legible-contrast threshold was calculated as the contrast boundary of 50% correct answer. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The findings from the review suggested that typefaces such as Verdana ( Chaparro, Shaikh, Chaparro, & Merkle, 2010 ; Franken, Podlesek, & Možina, 2015 ; Josephson, 2008 ) increased readability compared to Times New Roman and Arial, with bolded ( Silver & Braun, 1993 ), larger fonts ( Silver & Braun, 1993 ; Silver et al, 1994 ; Vigilante and Wogalter, 1999 ; Wogalter & Vigilante, 2003 ), and uppercase letters ( Ohyama & Sagawa, 2016 ) also aiding readability. Increasing white space around a message and using high contrasts such as black text on a white background could also enhance readability ( Arditi & Cho, 2007 ; Rousek & Hallbeck, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…The findings from the review suggested that typefaces such as Verdana ( Chaparro, Shaikh, Chaparro, & Merkle, 2010 ; Franken, Podlesek, & Možina, 2015 ; Josephson, 2008 ) increased readability compared to Times New Roman and Arial, with bolded ( Silver & Braun, 1993 ), larger fonts ( Silver & Braun, 1993 ; Silver et al, 1994 ; Vigilante and Wogalter, 1999 ; Wogalter & Vigilante, 2003 ), and uppercase letters ( Ohyama & Sagawa, 2016 ) also aiding readability. Increasing white space around a message and using high contrasts such as black text on a white background could also enhance readability ( Arditi & Cho, 2007 ; Rousek & Hallbeck, 2011 ).…”
Section: Methodsmentioning
confidence: 99%